Analisis Prosedur Pengembangan Bahan Ajar dalam Meningkatkan Kualitas Pembelajaran di SMK IT Arsitek Kota Bengkulu - Khairiah Khairiah; Chandra Novianto; Hamdan Junaidi (Al-Khair Journal: Management Education, 2026)
Abstrac: This study aims to describe, map, and analyze the teaching materials development procedure in an effort to improve the quality of learning at SMK IT Arsitek in Bengkulu City. Teaching materials development is crucial because it is a systematic design that facilitates the learning process to be more effective and responsive to student needs. The research method used is a descriptive qualitative approach. Primary data were obtained through interviews with the principal, vice principal, and teachers, while secondary data included documents such as the Syllabus, Lesson Plans, and Semester Programs. Data collection techniques were carried out through observation, interviews, and documentation, with data analysis using the Miles and Huberman model. The results of the study indicate that the teaching materials development procedure at SMK IT Arsitek is carried out independently by teachers through three main stages: analysis (identifying student behavior and characteristics), development (producing or revising materials), and evaluation and field trials. This process refers to the principles of the 2013 curriculum suitability, contextual materials, and strengthening Islamic values. The quality of learning at this school is determined by the competence of teachers, the majority of whom are certified, high student motivation in vocational practice, and adequate infrastructure support. The implementation of systematic procedures has been proven to increase the effectiveness and efficiency of learning, but the reality in the field shows that the consistency of teachers in updating or revising teaching materials periodically still needs to be improved to remain relevant to the needs of the business and industrial world (DUDI).Keywords: Development Procedures, Teaching Materials, Learning Quality. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan, memetakan, dan menganalisis prosedur pengembangan bahan ajar dalam upaya meningkatkan kualitas pembelajaran di SMK IT Arsitek Kota Bengkulu. Menggunakan metode kualitatif deskriptif. Sumber data dari data primer diperoleh melalui wawancara dengan kepala sekolah, wakil kepala sekolah, dan guru, sedangkan data sekunder mencakup dokumen seperti Silabus, RPP, dan Program Semester. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, dengan analisis data menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa prosedur pengembangan bahan ajar di SMK IT Arsitek dilakukan secara mandiri oleh guru melalui tiga tahapan utama: analisis (mengidentifikasi perilaku dan karakteristik siswa), pengembangan (memproduksi atau merevisi materi), serta evaluasi dan uji coba lapangan. Proses ini mengacu pada prinsip kesesuaian kurikulum 2013, materi yang kontekstual, dan penguatan nilai-nilai Islami. Kualitas pembelajaran di sekolah ini ditentukan oleh kompetensi guru yang mayoritas telah bersertifikasi, motivasi tinggi siswa dalam praktik kejuruan, serta dukungan sarana prasarana yang memadai. Dengan demikian dapat disimpulkan bahwa pengembangan bahan ajar sesuai prosedur terbukti meningkatkan efektivitas dan efisiensi pembelajaran, namun realita di lapangan menunjukkan bahwa konsistensi guru dalam memperbarui atau merevisi bahan ajar secara berkala masih perlu ditingkatkan agar tetap relevan dengan kebutuhan dunia usaha dan dunia industri (DUDI). Oleh karena itu dapat disarankan. Untuk meningkatkan kualitas pembelajaran maka tingkatkanlah pengembangan bahan ajar sesuai prosedur di sekolah.Kata kunci: Prosedur Pengembangan Bahan Ajar, Kualitas Pembelajaran.